DOPC versus DOPE as a helper lipid for gene-therapies: molecular dynamics simulations with DLin-MC3-DMA. Issue 48 (9th December 2020) - Ermilova, Inna; Swenson, Jan
Abstract : A comparison of behavior of DOPC and DOPE lipids in the shell of lipid nano-particles. Abstract : Ionizable lipids are important compounds of modern therapeutic lipid nano-particles (LNPs). One of the most promising ionizable lipids (or amine lipids) is DLin-MC3-DMA. Depending on their pharmaceutical application these LNPs can also contain various helper lipids, such as phospho- and pegylated lipids, cholesterol and nucleic acids as a cargo. Due to their complex compositions the structures of these therapeutics have not been refined properly. Therefore, the role of each lipid in the pharmacological properties of LNPs has not been determined. In this work an atomistic model for the neutral form of DLin-MC3-DMA was derived and all-atom molecular dynamics (MD) simulations were carried out in order to investigate the effect of the phospholipid headgroup on the possible properties of the shell-membranes of LNPs. Bilayers containing either DOPC or DOPE lipids at two different ratios of DLin-MC3-DMA (5 mol% and 15 mol%) were constructed and simulated at neutral pH 7.4. The results from the analysis of MD trajectories revealed that DOPE lipid headgroups associated strongly with lipid tails and carbonyl oxygens of DLin-MC3-DMA, while for DOPC lipid headgroups no significant associations were observed. Furthermore, the strong associations between DOPE and DLin-MC3-DMA result in the positioning of DLin-MC3-DMA at the surface of the membrane. Such an interplay between the lipids slows down the lateral diffusion of all simulated bilayers, where a more dramatic decrease of the diffusion rate is observed in membranes with DOPE. This can explain the low water penetration of lipid bilayers with phosphatidylethanolamines and, probably, can relate to the bad transfection properties of LNPs with DOPE and DLin-MC3-DMA.